Lightness Discrimination Depends More on Bright Rather Than Shaded Regions of Three-Dimensional Objects. (November 2019) - Toscani, Matteo; Valsecchi, Matteo
The brighter portions of a shaded complex object are in principle more informative about its lightness and are preferentially fixated during lightness judgments. In this study, we investigate whether preventing this strategy also has measurable detrimental effects on performance. Observers were presented with a reference and a comparison three-dimensional rendered object and had to choose which one was "painted with a lighter gray." The comparison was rendered with different diffuse reflectance values. We compared precision between three different conditions: full image, 20% of the lightest pixels removed, or 20% of the darkest pixels removed. Removing the bright pixels maximally impaired performance. The results confirm that the strategy of relying on the brightest areas of a complex object in order to estimate lightness is functionally optimal, yielding more precise representations.